Manajemen Pembelajaran Berbasis Boarding School: Studi Multi Kasus SMP Plus Al Ishlah Prambontergayang Soko Tuban dan SMP Plus Matholi’ul Anwar Maibit Rengel Tuban - Ahmad Isro' Nurul Huda (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
The purpose of this article is to identify and describe the planning, implementation and evaluation of boarding school learning at SMP Plus Al Ishlah Prambontergayang Soko Tuban and SMP Plus Matholi'ul Anwar Maibit Rengel Tuban. The type of research used is qualitative research with a case study approach. Researchers collected data using three techniques, namely: in-depth interviews, involved observation and documentation. Data analysis was carried out using three steps, namely: data reduction, data presentation, drawing conclusions. The results of this study are: 1) The planning carried out at SMP Plus Al Ishlah has referred to the vision, mission and goals as well as content standards by involving all existing stakeholders. Meanwhile, the planning at SMP Plus Matholi'ul Anwar is always adjusted to the activities of the pesantren by taking into account the standards of content and the level of needs of students in the school. 2) The learning carried out at SMP Plus Al Ishlah is a combination of the formal curriculum and the pesantren curriculum. While the learning carried out at SMP Plus Matholi'ul Anwar cannot be separated from all parties, both internal and external to the school, so that good cooperation and coordination is needed between the school and parents, the community and so on. 3) Evaluation at SMP Plus Al Ishlah is carried out directly by the principal assisted by the waka-waka and the ranks of the mudirul 'am, because this institution is designed under the auspices of the Islamic boarding school so that the mudirul 'am also participates in controlling and coloring several policies related to schools. Meanwhile, at SMP Plus Matholi'ul Anwar, a thorough evaluation is carried out in every field through joint meetings or coordination meetings